KORESPONDENSI REVITALISASI NILAI-NILAI ETIKA KEAGAMAAN SISWA SMA DI ERA GLOBALISASI MELALUI REFLEKSI TOKOH SENTRAL NABI MUHAMMAD SAW - Niswah Hasanah (Sekolah Tinggi Agama ISLAM PANCA BUDI PERDAGANGAN, 2023)
Revitalization of ethical religious values among high school students in the era of globalization through the reflection of the central figure of Prophet Muhammad SAW is an essential endeavor. Educating on the values of religious ethics, particularly within the context of Islam, can be achieved by focusing on reflections based on the teachings of the central figure, Prophet Muhammad SAW. Prophet Muhammad serves as the prime example for the Islamic community in various aspects of life. By reflecting upon his teachings and actions, students can gain profound insight into moral principles relevant to the challenges of the present era. Globalization brings about intricate influences, and through the reflection of Prophet Muhammad's teachings, students can comprehend how he faced changes and challenges in his time. Emphasis on values such as honesty, tolerance, compassion, and justice taught by Prophet Muhammad can form the foundation for students to confront a multitude of situations in the globalization era filled with diverse perspectives and values. Moral education based on the teachings of Prophet Muhammad can also assist students in understanding the importance of respecting differences among individuals and cultures. This is key in navigating the complexity of globalization without losing one's identity and cherished principles. By integrating Islamic teachings practiced by Prophet Muhammad into their everyday lives, students can comprehend that religious ethical values are not archaic or detached from the global reality but are relevant and crucial in molding individuals with noble character in the modern era. In conclusion, through reflecting on the exemplar of Prophet Muhammad SAW, students can gain profound understanding of the ethical religious values pertinent in addressing the complexity and challenges of the globalization era. This enables them to become responsible, ethical, and highly competitive individuals in this ever-evolving era.